2009
DOI: 10.1088/0953-8984/21/41/415701
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between magnetism and superconductivity and the appearance of a second superconducting transition in α-FeSe at high pressure

Abstract: We synthesized tetragonal a-FeSe by melting a powder mixture of iron and selenium at high pressure. Subsequent annealing at normal pressure results in removing traces of hexagonal bFeSe, formation of a rather sharp transition to superconducting state at T c ~ 7 K, and the appearance of a magnetic transition near T M = 120 K. Resistivity and ac-susceptibility were measured on the annealed sample at hydrostatic pressure up to 4.5 GPa. A magnetic transition visible in ac-susceptibility shifts down under pressure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Other kind of anomaly commonly observed in the superconducting FeSe samples is a step-like change in the magnetization curve in the ZFC measurement ending around 120 K-130 K [4,7,21], similar to that observed in figure 3 for the commercial sample. Blachowski, et al [20] have reported this kind of anomaly and by means of Mössbauer experiments analysis they adjudicated it to the presence of a hexagonal FeSe phase, specifically to spin rotation transition around 125 K in the hexagonal Fe 7 Se 8 compound.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Other kind of anomaly commonly observed in the superconducting FeSe samples is a step-like change in the magnetization curve in the ZFC measurement ending around 120 K-130 K [4,7,21], similar to that observed in figure 3 for the commercial sample. Blachowski, et al [20] have reported this kind of anomaly and by means of Mössbauer experiments analysis they adjudicated it to the presence of a hexagonal FeSe phase, specifically to spin rotation transition around 125 K in the hexagonal Fe 7 Se 8 compound.…”
Section: Discussionsupporting
confidence: 79%
“…The critical temperature is around 8 K, but can be increased with pressure reaching a maximum of about 37 K at 7 GPa [2][3][4][5][6][7][8][9][10][11]. It is found that in cooling, FeSe presents a structural transition from tetragonal to orthorhombic.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the change between 2 GPa and 3 GPa is drastic, implying a phase transition between different superconducting states. The possibility of two kinds of superconducting phases has also been reported by Sidorov et al, 22 indicated by the jump in dρ/dT . A linear dependence of electrical resistivities on temperature is commonly observed in cuprate superconductors [23][24][25] and is considered to be one of the primary indicators of non-Fermi-liquid behavior; an incoherent scattering of fermion quasiparticles via magnetic interactions leads to resistivity of the form ρ(T ) = ρ 0 + AT α where ρ 0 , A and α are arbitrary constants, however, no linear term is expected according to conventional Fermi-liquid theory.…”
Section: Resultsmentioning
confidence: 52%
“…AC susceptibility measurements were done with a SR830 lock-in amplifier in a large compensated coil system (see [18] for more details).…”
Section: Methodsmentioning
confidence: 99%